PRP-Induced Lichen Scleroatrophicus - Özkoca, Defne; Üstünbaş Uzunçakmak, Tuğba Kevser; Kutlubay, Zekayi (Cerrahpaşa Medical Journal, 2021)
Lichen scleroatrophicus is a chronic inflammatory skin disease that is usually observed in the female external genital tract. Ivory-white atrophic plaques are the hallmark of the disease. Here, we present a case of extragenital lichen scleroatrophicus in a patient with a history of multiple PRP treatments for knee osteoarthritis. There are no reported cases of lichen scleroatrophicus due to platelet-rich plasma therapy in the literature. Indeed, platelet-rich plasma has been used in the treatment of genital lichenscleroatrophicus. Cite this article as: Özkoca D, Uzunçakmak TKÜ, Kutlubay Z. PRP-induced lichen scleroatrophicus. Cerrahpaşa Med J. 2022;46(1):78-79.